Effect of L-Arginine on Titin Expression in Rat Soleus Muscle After Hindlimb Unloading - Ulanova, Anna; Gritsyna, Yuliya; Salmov, Nikolai; Lomonosova, Yuliya; Belova, Svetlana; Nemirovskaya, Tatyana; Shenkman, Boris; Vikhlyantsev, Ivan (Frontiers in Physiology, 2019)
Nitric oxide (NO), produced by NO-synthases via L-arginine oxidation, is an essential trigger for signaling processes involved in structural and metabolic changes in muscle fibers. Recently, it was shown that L-arginine administration prevented the decrease in levels of the muscle cytoskeletal proteins, desmin and dystrophin, in rat soleus muscle after 14 days of hindlimb unloading. Therefore, in this study, we investigated the effect of L-arginine administration on the degree of atrophy changes in the rat soleus muscles under unloading conditions, and on the content, gene expression, and phosphorylation level of titin, the giant protein of striated muscles, able to form a third type of myofilaments—elastic filaments. A 7-day gravitational unloading (hindlimb suspension (HS) group) resulted in a decrease in the soleus weight:body weight ratio (by 31.8%, р < 0.05), indicating muscle atrophy development. The content of intact titin (T1) decreased (by 22.4%, р < 0.05) and the content of proteolytic fragments of titin (T2) increased (by 66.7%, р < 0.05) in the soleus muscle of hindlimb suspension rats, compared to control rats. The titin gene expression and phosphorylation level of titin between these two groups were not significantly different. L-Arginine administration under 7-day gravitational unloading decreased the degree of atrophy changes and also prevented the decrease in levels of T1 in the soleus muscle as compared to HS group. Furthermore, L-arginine administration under unloading resulted in increased titin mRNA level (by 76%, р < 0.05) and decreased phosphorylation level of T2 (by 28%, р < 0.05), compared to those in the HS group. These results suggest that administration of L-arginine, the nitric oxide precursor, under unloading decreased the degree of atrophy changes, increased gene expression of titin and prevented the decrease in levels of T1 in the rat soleus muscle. The results can be used to search for approaches to reduce the development of negative changes caused by gravitational unloading in the muscle.